Feldspar Dissolution and Its Influence on Reservoirs: A Case Study of the Lower Triassic Baikouquan Formation in the Northwest Margin of the Junggar Basin, China. (24th September 2018) - Xiao, Meng; Yuan, Xuanjun; Cheng, Dawei; Wu, Songtao; Cao, Zhenglin; Tang, Yong; Xie, Zongrui
Abstract : Feldspar dissolution is a common feature in clastic rock reservoirs of petroliferous basins and has an important influence on reservoir quality. However, the effect of feldspar dissolution on reservoir quality varies under different depositional environments and diagenetic systems. The study area in this paper is located in the Baikouquan Formation in the northwestern margin of the Junggar Basin, which is significantly influenced by feldspar dissolution. Based on the analyses of core and thin section observations, QEMSEM, XRD, SEM, CL, fluorescence, and image analysis software combined with logging and physical property data, this study shows that feldspar dissolution in the subaqueous distributary channel of a fan delta plain, which has good original physical properties and low mud contents, significantly improves the properties of the reservoir. The main reasons for this are as follows: (1) the sedimentary facies with good original properties and low mud content is a relatively open system in the burial stage. The acidic fluids needed for feldspar dissolution are mostly derived from organic acids associated with the source rocks and migrate to the good-permeability area of the reservoir; (2) the by-products of feldspar dissolution, such as authigenic clay minerals and authigenic quartz, are transported by pore water in a relatively open diagenetic system and then precipitated in a relatively closed diagenetic system; and (3) the clay minerals produced by feldspar dissolution in different diagenetic environments and diagenetic stages have different effects on the reservoir. When the kaolinite content is less than 3%, the illite content is less than 4%, and the chlorite content is less than 12%, the clay minerals have a positive effect on the porosity. These clay minerals can reduce porosity and block pore throats when their contents are larger than these values.